Determinants of Awareness to Invest in Shariah-based Private Retirement Scheme (PRS): The Case of Public University Students in Malaysia - Yahaya, Solehah; Ibrahim, Haslindar (School of Social Sciences, USM, 2017)
This study aims to identify four determinants that influencing students’ intention to invest into Shariahbased Private Retirement Scheme (PRS) in Malaysia among public university students. The purpose of this study is to identify the relationship between determinant namely attitude, social influence, religious obligation, and government support on intention to invest into Shariah-based PRS. The sample comprised of 370 students who were taking business courses in their programme. By using survey as a method to collect the data, the study found that all four determinants have significant influence on the awareness to invest in Shariah-based PRS. In addition, these findings will enhance the students’ awareness, knowledge and understanding of the importance of having a good financial planning for their retirement once they start their career.